Нотатки з латинської епіграфіки Херсонеса і Харакса - Зубар, В.М. (Археологія, 1990)
У статті аналізуються три латинських написи з Херсонеса і одна з Харакса, знайдені у дореволюційний період. На підставі палеографії написів, а також порівняльного матеріалу автор робить спробу дати нове датування та інтерпретацію цих пам’яток. В статье рассмотрены три латинских надписи из Херсонеса и одна из Харакса, которые были найдены в дореволюционный период и неоднократно публиковались рядом исследователей. На основании анализа времени появления в латинских надгробных эпитафиях формулы О. М. и разделителей в виде «листиков», автор приходит к выводу о том, что надгробие вольноотпущенников, убитых таврами (IOSPE, I², № 562), следует датировать не серединой I в., а второй половиной II в. Исходя из мест дислокации I когорты Бракаравгустанов и I когорты Бракаров, В. М. Зубарь считает, что солдат Марк Мецилий служил в I когорте Бракаров (IOSPE, I², № 553), а когорта I Бракаравгустанов во второй половине II в. находилась на территории Дакии и из ее состава не могли откомандировываться солдаты для несения службы в Херсонесе. В статье также анализируется латинская надпись, новое чтение которой недавно было предложено Г. Альфёльди (IOSPE, I², № 572; Шангин М. А. ВДИ, 1938, № 3). На основании изучения палеографии, а также сравнительного материала, автор приходит к выводу о том, что в ней нельзя восстанавливать название легиона II Негси-Нае и использовать указанные памятники в качестве доказательства присутствия регулярных римских воинских подразделений в Херсонесе в конце III—IV вв. На базе новых исторических разработок Р. Сайма и билингвы из Том в статье рассматривается также новая датировка алтаря с посвящением Юпитеру от имени М. Геминея Фортиса в тесной связи с политикой Рима в Северном Причерноморье. The paper deals with three Latin inscriptions from Khersones and one from Kharax which were found in the prerevolutionary period and published for many times by some researchers. Coming from the analysis of a period when a formula D.M. and dividers shaped as “leaves” appeared in Latin epitaphs, the author concludes that the gravestone of freedmen killed by taurs (IOSPE, I², № 562) should be dated by the second half of the 2nd cent., rather than by the mid of the 1st cent. Proceeding from the disloca-tion places of cohort I of the Brakaraugustans and cohort I of the Brakars, V. M. Zubar considers that soldier Mark Mecylij served in cohort I of the Brakars (IOSPE, I², No. 553) and cohort I of the Brakaraugustans in the second half of the 2nd cent, was in the territory of Dakiya and soldiers who served in it could not be sent for service to Khersones. A new reading of the Latin inscription suggested recently by G. Alfoldi (IOSPE, Shangin, 1938, No. 9) is analyzed. Proceeding from the study of paleography and comparative data, the author makes a conclusion that the title of legion II Herculiae must not be restored in that inscription and so the mentioned monuments must not be used as a proof of the presence of regular Roman military subunits in Khersones in late 3d-4th cent. Basing on new historical studies of R. Saim and bilingua from Tomhy a new dating of altar with dedication to Jupiter from M. Heminey Fortis is considered as tightly related to the Rome policy in the Northern Black Sea territory.